Use of a Feedback Survey as a Part of a Wellness Champions Program to Improve Academic Faculty Satisfaction and Burnout: Implications for Burnout in Academic Health Centers - Amy Beth Locke MD, FAAFP; Katherine T Fortenberry PhD; Erika Sullivan MD; Dominik Ose DrPH, MPH; Ben Tingey; Fares Qeadan PhD; Autumn Henson BS; Sonja Van Hala MD, MPH, FAAFP (SAGE Publishing, 2020)
Background Faculty and trainee well-being at academic medical centers is a nationwide concern. In response, the University of Utah Health created a system-wide provider wellness program that used individual faculty champions who were empowered to 1) examine the unique needs of their department or division using a lens of quality improvement, 2) design projects to address well-being, and 3) measure impact of projects addressing well-being. One team used a feedback tool to attempt to improve the well-being of Family Medicine faculty by better understanding challenges and developing a roadmap for action. Objective Evaluate the effectiveness of an anonymous feedback tool on faculty well-being. Methods The Division of Family Medicine developed and implemented a quarterly anonymous faculty survey to facilitate an ongoing improvement process for faculty wellness in 2016. The faculty survey identified thematic concerns, which were used to develop constructive solutions and systemic changes. Results A closed loop feedback structure provided rich faculty input into impacts on burnout and professional well-being. Sense of control (good to optimal) over workload among faculty increased significantly (p = 0.011) from 10% to 42% over one year exhibiting a large effect size (Cohen's h = 0.751). Faculty burnout, using a single item emotional exhaustion question validated to the Maslach Burnout Inventory, was reduced from 48% to 25% showing a medium effect size (Cohen's h = 0.490 with p = 0.097). Work related stress was reduced from 72% to 50% demonstrating clinical significance (Cohen's h = 0.465) but not statistical significance (p = 0.154)-an effect which was more noticeable when comparing means between years (Cohen's d=0.451with p = 0.068). Response rate was 100% in 2016 (29/29) and 92% (23/25) in 2017. Conclusion This faculty survey, which has since been adopted by other groups at the University of Utah, could help improve well-being in a variety of health care professions.